HUMAN RESOURCE MANAGEMENT IN EDUCATIONAL INSTITUTIONS: CONCEPTS AND ITS URGENCY - Zikra Maulana; Musyarapah (STAI Ma'had Aly Al-Hikam Malang, 2025)
Human resource management (HRM) plays a strategic role in determining the success of educational institutions since educational quality is highly influenced by the performance and competence of teachers and educational staff. This article aims to analyze the concept, implementation, and urgency of human resource management in improving educational quality, particularly in Islamic educational institutions. The study employs a qualitative approach through a literature review of relevant national and international sources. The results reveal that HRM in education functions not only administratively but also encompasses professional and spiritual dimensions. Its implementation includes workforce planning, competency-based recruitment, continuous training, objective performance appraisal, and fair reward systems. In the context of Islamic education, HRM should be grounded in the values of sincerity, trustworthiness, responsibility, and cooperation (ta‘awun). Current challenges in HRM involve teachers’ readiness for the digital era, inadequate welfare, and weak career development systems. This study concludes that strengthening HRM through professionalism, welfare, and work spirituality is crucial in building excellent and character-based educational institutions. An effective and value-oriented HRM system can produce competent, loyal, and highly ethical educators, which in turn contributes significantly to the enhancement of national education quality. Keywords: Human resource management, Islamic education, education quality, professionalism, work spirituality. Abstrak Manajemen sumber daya manusia (MSDM) memiliki peran strategis dalam menentukan keberhasilan lembaga pendidikan, karena kualitas pendidikan sangat dipengaruhi oleh kinerja dan kompetensi tenaga pendidik serta tenaga kependidikan. Artikel ini bertujuan untuk menganalisis konsep, implementasi, dan urgensi manajemen sumber daya manusia dalam meningkatkan mutu pendidikan, khususnya pada lembaga pendidikan Islam. Penelitian menggunakan pendekatan kualitatif dengan metode studi kepustakaan terhadap berbagai buku dan jurnal nasional maupun internasional yang relevan Hasil kajian menunjukkan bahwa MSDM dalam pendidikan tidak hanya berfungsi secara administratif, tetapi juga mencakup dimensi profesional dan spiritual. Implementasi MSDM mencakup perencanaan tenaga kerja, rekrutmen berbasis kompetensi, pelatihan berkelanjutan, penilaian kinerja objektif, dan pemberian penghargaan yang adil. Dalam konteks pendidikan Islam, MSDM harus berlandaskan nilai-nilai keikhlasan, amanah, tanggung jawab, dan kerja sama (ta‘awun). Tantangan utama MSDM saat ini terletak pada kesiapan tenaga pendidik menghadapi era digital, rendahnya kesejahteraan, serta lemahnya sistem pengembangan karier. Artikel ini menyimpulkan bahwa penguatan MSDM melalui profesionalitas, kesejahteraan, dan spiritualitas kerja menjadi kunci dalam membangun lembaga pendidikan yang unggul dan berkarakter. MSDM yang efektif dan berbasis nilai mampu menghasilkan tenaga pendidik yang kompeten, loyal, serta berintegritas tinggi, sehingga berdampak signifikan terhadap peningkatan mutu pendidikan nasional. Kata Kunci: Manajemen sumber daya manusia, pendidikan Islam, mutu pendidikan, profesionalitas, spiritualitas kerja.